Analysis Of The Financial Performance Of Trading Companies At Pt Nippon Indosari Corpindo TBK - Elan Margareth Simbolon; Muhammad Guntur; Putri Telaumbanua; Renny Maisyarah (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the financial performance of PT Nippon Indosari Corpindo Tbk as a modern bread manufacturing company in Indonesia. The research employs a quantitative method with an observational approach. The data used are secondary data obtained from the company’s annual financial statements for the period 2021–2023. Data analysis is conducted using financial ratios, including liquidity, profitability, and activity ratios, to assess the company’s financial health. The results indicate that PT Nippon Indosari Corpindo Tbk has a strong and stable level of liquidity, reflecting the company’s ability to meet its short-term obligations. In addition, the company’s profitability has increased, as indicated by improvements in Net Profit Margin, Return on Assets, and Return on Equity, which demonstrate the company’s success in increasing profits through sales recovery and production cost efficiency. From an operational activity perspective, the increase in inventory turnover and total asset turnover indicates that the company has become more efficient in managing inventory and utilizing assets to generate revenue. Overall, the findings show that PT Nippon Indosari Corpindo Tbk is in a healthy financial condition and has favorable growth prospects.